"Ask, don't just answer": Eliciting informational and emotional support needs in health-care encounters. Issue 4 (2nd October 2021) - Donovan, Erin E.; Quaack, Karly R.; Brown, Laura E.
Abstract : Courses: Interpersonal Health Communication, Communication in Health Care Settings. Objectives: This lesson is designed for health profession students whose work will involve direct interaction with patients. It is designed to help students (a) better understand how to diagnose patients' needs for both informational and emotional support when responding to questions, and (b) practice skills for doing so.